Death and dying during the COVID-19-pandemic – A qualitative evaluation of stress factors for nursing staff - Lea Kiefer; Stefan Bösner; Jan Adriaan Graw; Christian Volberg (Palliative Care and Social Practice, 2025)
Background: The COVID-19 pandemic posed an unprecedented challenge for the healthcare system worldwide and led to high levels of psychosocial stress, particularly among nursing staff working in special COVID-19 wards. As previous studies have shown, this stress has had a profound impact on mental health, underscoring the need for further research to deepen our understanding of these effects. Objectives: To investigate the experiences of nursing staff working on special COVID-19 wards during the COVID-19 pandemic with regard to the death and dying of patients. Methods: To uncover aspects that might have remained unobserved in a quantitative survey, a qualitative research design was chosen for data collection. Using a semi-structured interview guide, we interviewed 14 nurses about their experiences. The data was then analysed using a qualitative content analysis according to Mayring. Results: Nursing staff were exposed to a particularly high level of stress. The reasons for this included the lack of opportunities for end-of-life care, patients dying alone, an above-average level of confrontation with death and serious disease progression and finally, limited treatment options and specialised care for deceased patients. These factors led to moral injuries. Conclusion: The results emphasise the urgency of better preparing nursing staff for future crises, providing psychosocial support and developing preventive strategies against moral distress. The promotion of resilience and the creation of conditions that prevent moral injury are essential to minimise the long-term effects of such stress and to protect the mental health of nursing staff in the long term. Trial registration: Registered in the German Register of Clinical Studies under the number DRKS00030425.